Establishing an Organotypic System for Investigating Multimodal Neural Repair Effects of Human Mesenchymal Stromal Stem Cells. (18th July 2018) - Thakor, Devang K.; Wang, Lei; Benedict, Darcy; Kabatas, Serdar; Zafonte, Ross D.; Teng, Yang D.
Abstract: Human mesenchymal stromal stem cells (hMSCs) hold regenerative medicine potential due to their availability, in vitro expansion readiness, and autologous feasibility. For neural repair, hMSCs show translational value in research on stroke, spinal cord injury (SCI), and traumatic brain injury. It is pivotal to establish multimodal in vitro systems to investigate molecular mechanisms underlying neural actions of hMSCs. Here, we describe a platform protocol on how to set up organotypic co‐cultures of hMSCs (alone or polymer‐scaffolded) with explanted adult rat dorsal root ganglia (DRGs) to determine neural injury and recovery events for designing implants to counteract neurotrauma sequelae. We emphasize in vitro hMSC propagation, polymer scaffolding, hMSC stemness maintenance, hMSC‐DRG interaction profiling, and analytical formulas of neuroinflammation, trophic factor expression, DRG neurite outgrowth and tropic tracking, and in vivo verification of tailored implants in rodent models of SCI. © 2018 by John Wiley & Sons, Inc.